The Clinical Utility of Non-invasive Prenatal Testing for Pregnant Women With Different Diagnostic Indications - Zheng, Jianli; Lu, Haiyan; Li, Min; Guan, Yongjuan; Yang, Fangfang; Xu, Mengjun; Dong, Jingjing; Zhang, Qinge; An, Ning; Zhou, Yun (Frontiers in Genetics, 2020)
Background: Our aim was to evaluate the clinical utility of noninvasive prenatal testing for pregnant women with different diagnostic indications. Methods: In eight counties and districts of Yancheng, we studied 13,149 pregnant women with different indications who were offered NIPT for fetal screening, including for sex chromosomal aneuploidiers (SCAs), rare autosomal trisomies (RATs) and subchromosomal copy number variations (CNVs). The purpose was to compare the detection of positive predictive values (PPVs) of different indications with the use of NIPT. The results were validated by karyotyping, chromosome microarray analysis (CMA) or follow-up of pregnancy outcomes. Results: 13,149 maternal plasma samples were sequenced, among which 28 samples (0.2%) failed the sequencing quality control. The remaining 13,121 samples were analyzed, and birth follow-up missed 2192 samples (16.7%). The positive predictive values (PPVs) of NIPT results for trisomy 21, 18 and SCAs were 96.67%, 63.64% and 31.34%, respectively. Among the advanced maternal age (AMA), serum screening high risk (SSHR), serum screening intermediate risk (SSIR) and voluntary screening (VS) groups, the PPVs for the common trisomies were 81.25%, 85.71%, 100% and 70%, respectively; the PPVs for total chromosomal abnormalities were 55.82%, 65.22%, 23.08% and 36.59%, respectively. Conclusions: NIPT for trisomy 21, 18 and SCAs screening were ideal, and the PPVs for trisomy 13, RATs and CNVs were low. For the AMA and VS groups, NIPT could be used as a first-line screening program; for SSHR and SSIR groups, NIPT could be used as a second-line supplementary screening program.